The influence of third generation artificial soccer turf characteristics on ground reaction forces during running - Meijer, K.; Dethmers, J.; Savelberg, H.; Willems, P.; Wijers, B. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to determine the effect of different artificial soccer turf pitches on the ground reaction forces of running soccer players. For this purpose ground reaction forces were determined for twenty soccer players while they ran at three different speeds across a 25 meter long track covered with a third generation artificial soccer turf. Three different pitches, two FIFA 1star and one FIFA 2star, were examined. There was no difference between the two 1star systems in the peak vertical and horizontal ground reactions forces. Data on the 2star system was equivocal due to a too small sample size. It is concluded that surface characteristics influence the loading of the human muscleskeletal system more subtly than initially anticipated. A more detailed biomechanical analysis of the events during impact is required to identify the critical loading parameters.